Iot-Enabled Home Environment Control for Next Generations - B Sravan Kumar, M Madhu Babu, G Saisravanthi, P Prakash (Mathematical Statistician and Engineering Applications, 2023)
People have become more conscious of the environment in recent years. This awareness drives the need for a dependable environmental monitoring system. A system for monitoring the environment’s air quality is also employed in industry. In heavy industrial or mining, Several harmful gases have the potential to contaminate the air. Users can monitor temperature and humidity levels as well as detect the presence of hazardous gases in both indoor and outdoor spaces with the help of the suggested module. The information is accessible to the user from anywhere in the globe with an internet connection thanks to the web server’s storage of it. The suggested work develops a web application that provides users with access to essential data. The user also has the option of configuring a notification for significant changes in sensor data. The proposed system is accurate, user-friendly, and less expensive than other systems that are closely linked. Additionally cloud-based, it has modules for data monitoring and visualisation. In stages, the system has been assessed. After evaluating all features under various circumstances, it exhibits a high level of accuracy and dependability.